Bone Status in Patients with Epilepsy: Relationship to Markers of Bone Remodeling - Hamed, Sherifa A.; Moussa, Ehab M. M.; Youssef, Ahmad H.; Abd ElHameed, Mohammed A.; NasrEldin, Eman (Frontiers in Neurology, 2014)
Patients with epilepsy and treated with antiepileptic drugs (AEDs) may develop metabolic bone disease, however, the exact pathogenesis of bone loss with AEDs is still unclear. Included were 75 adults with epilepsy (mean age: 31.90±5.62years; duration of treatment with AEDs: 10.57±3.55years) and 40 matched healthy controls. Bone mineral content (BMC) and densities (BMD) of the femoral neck and lumbar spine were measured using dual energy X-ray absorptiometry (DEXA). Blood samples were analyzed for calcium, magnesium, phosphate, alkaline phosphatase (ALP), 25-hydroxy vitamin D (25OHD), soluble receptor activator of nuclear factor kB ligand (sRANKL), osteoprotegerin (OPG) and OPG/RANKL ratio (markers of bone remodeling). Compared to controls, patients had lower BMD, BMC, Z-score and T-score at the femoral neck and lumbar spine (all p<0.001). 72% and 29.33% of patients had osteoporosis of the lumbar spine and femoral neck. Patients had significantly lower serum calcium, 25(OH)D and OPG and higher ALP, sRANKL levels and sRANKL/OPG (all p<0.001). 52% of patients had hypocalcemia, 93% had hypovitaminosis D, 31% had high levels of sRANKL and 49% had low levels of OPG. No differences were identified between DEXA and laboratory results in relation to the type, dose or serum levels of AEDs. BMD at the femoral neck and lumbar spine were found to be correlated with the duration of illness (p=0.043; p=0.010), duration of treatment with AEDs (p<0.001; p=0.012) and serum levels of 25(OH)D (p<0.042; p=0.010), sRANKLs (p=0.005; p=0.01) and OPG (p<0.006; p<0.01). In linear regression analysis and after adjusting for gender, age, weight, duration and number of AEDs, we observed an association between BMD, 25(OH)D (p=0.04) and sRANKL (p=0.03) concentrations. We conclude that AEDs may compromise bone health through disturbance of mineral metabolism and acceleration of bone turnover mechanisms.